Photonic Instrumentation Engineering IX 2022
DOI: 10.1117/12.2608424
|View full text |Cite
|
Sign up to set email alerts
|

Realizing a robust, reconfigurable active quenching design for multiple architectures of single-photon avalanche detectors

Abstract: Most active quench circuits used for single-photon avalanche detectors are designed either with discrete components which lack the flexibility of dynamically changing the control parameters, or with custom ASICs which require a long development time and high cost. As an alternative, we present a reconfigurable and robust hybrid design implemented using a System-on-Chip (SoC), which integrates both an FPGA and a microcontroller. We take advantage of the FPGA's speed and configuration capabilities to vary the qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recently, active quenching and reset (AQR) configurations have been widely used due to their fast response, small area, and configurable dead time. The quenching and resetting times have evolved from the microseconds range in passive configuration to several nanoseconds in recent active configurations [ 28 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. To simulate the performance of these advanced front-end circuits, SPAD circuit models are needed.…”
Section: Spad Circuit Modelsmentioning
confidence: 99%
“…Recently, active quenching and reset (AQR) configurations have been widely used due to their fast response, small area, and configurable dead time. The quenching and resetting times have evolved from the microseconds range in passive configuration to several nanoseconds in recent active configurations [ 28 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. To simulate the performance of these advanced front-end circuits, SPAD circuit models are needed.…”
Section: Spad Circuit Modelsmentioning
confidence: 99%
“…Samuel Burri et al reported a compact linear SPAD camera system with commercial FPGA-based TDC modules for versatile 50 ps resolution timeresolved imaging; however, the variable-load quenching circuit used to implement the quenching process of the SPAD array was designed based on ASIC technology [9]. Subash Sachidananda et al reported a reconfigurable hybrid design implemented by a System-on-Chip (SoC), which integrates an FPGA to vary the quench and reset parameters; however, it practically belongs to the ASIC-based AQC category [10].…”
Section: Introductionmentioning
confidence: 99%